KEPUTUSAN PEMBELIAN DITINJAU DARI KUALITAS PRODUK, CITRA MEREK DAN FASILITAS PADA ABATA DONUT’S SURAKARTA - Sandra Amelinda Kundari (JURNAL ILMIAH EDUNOMIKA, 2021)
Competition in the culinary business is currently required for business actors to have a strategy that is able to attract and retain consumers for the sustainability of their company. This study aims to test product quality, brand image and facilities simultaneously influence Abata Donut's purchasing decisions. The sample research sample is 100 consumers accidental sampling with multiple linear regression method. The results of the research on product quality, brand image and facilities simultaneously and partially have a significant effect on Abata Donut's purchasing decisions. The contribution of the three independent variables can explain the purchase decision by 42.9% and the rest is influenced by other variables. Keywords: product quality; brand image; facilities; customer satisfaction